Kristy Kowal at 40 m of Her Leg of the 4 x 100 m Medley Relay Gold Medal Race at the 1998 Perth World Championships - Rushall, B. S. (1999)
Video pictures (15 frames) and the appropriate technical/ biomechanical explanations for Kristy Kowal at 40 m of Her Leg of the 4 x 100 m Medley Relay Gold Medal Race at the 1998 Perth World Championships. This analysis provides another perspective of Kristy Kowal's "drag-force breaststroke." It demonstrates an alternative and very different model to the more traditional outsweep-insweep lift-force-arm-movement form of the stroke. The swimmer's streamlining, orce-generation, use of the forearm/hand surfaces for propulsion, and direct kick are worthy of emulation.